The Effect of Implementation of The Hope Family Program on The Fulfillment of Basic Food Needs of Beneficiaries Family During The Covid-19 Pandemic in Jatisampurna District, Bekasi City - Badruddin, Syamsiah; Nugraha, Muhammad Nata (Journal Socio Humanities Review, 2022)
The Covid-19 virus has an impact on the loss of livelihoods and income for some people. As a government effort to ease the burden of spending on the poor and vulnerable who have been designated as Beneficiary Families in meeting their family's food needs, the government provides Non-Cash Food Assistance through the Family Hope Program and increases the amount of assistance provided to the poor and vulnerable during the Covid-19 pandemic. 19. This research uses descriptive quantitative method. Beneficiary families become respondents in this study. This study uses Structural Functional theory where all elements in society function with each other so that society carries out its functions properly, therefore community needs are conditions that must be adapted from the existing social system so that the function of the structure can run according to its function. Based on the results of the analysis obtained, it can be seen that the Family Hope Program has a positive and strong influence in meeting the basic food needs of the Beneficiary Families